Comparison of Pain Response to Venepuncture Versus Heel Lance Blood Sampling in Term Neonates - Shrestha, M; Adhikari, RK (Journal of Nepal Paediatric Society, 2012)
Introduction: Pain in neonates is largely underestimated and neglected. Pain experience can alter clinical outcome, brain development and subsequent behavior in newborns. Numerous newborns undergo blood sampling routinely in nurseries/NICUs and these procedures are often done without pain relieving measures. Heel lancing and venepuncture are two common procedures for blood sampling in neonates. The objective of this study was to compare pain response to venepuncture versus heel lance in full term neonates. Materials and Methods: A comparative observational study was conducted among 200 term neonates who were undergoing blood sampling for bilirubin or glucose estimation. Neonates were randomly assigned to heel lance (HL) and venepuncture (VP) groups with 100 babies in each group. During the procedure, pain was assessed by Neonatal/Infant pain Scale (NIPS). Heart rate (HR) and oxygen saturation (SpO2) were continuously monitored 5 minutes prior to procedure and upto 5 minutes after the procedure. Results: The median NIPS score in HL and VP were 7 and 3.5 respectively which showed statistically significant (p= 0.0001) higher level of pain experience in HL than in VP. During the procedure, both the groups (HL and VP) showed significant changes in heart rate and oxygen saturation i.e., increase in HR (p= 0.0001) and decrease in SpO2 (p= 0.0001), however the increase in heart rate and decrease in oxygen saturation were significantly more in HL than in VP (p= 0.0001). Conclusion: Neonates perceive pain as demonstrated by Neonatal Pain Scale and venepuncture is the less painful procedure than heel lancing for blood sampling in neonates. J. Nepal Paediatr. Soc. 32(2) 2012 99-104 doi: http://dx.doi.org/10.3126/jnps.v32i2.5477